2021
DOI: 10.4037/ccn2021189
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Intubation Time in Adult Cardiothoracic Surgery Patients With a Fast-track Extubation Protocol

Abstract: Background Prolonged intubation after cardiac surgery increases the risk of morbidity and mortality and lengthens hospital stays. Factors that influence the ability to extubate patients with speed and efficiency include the operation, the patient’s baseline physiological condition, workflow processes, and provider practice patterns. Local Problem Progression to extubation lacked consistency and coordination across the team. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Patients with early extubation had shorter ICU and hospital stays [37]. Ellis et al demonstrated that after implementing a fast-track extubation protocol, the number of early extubations after cardiac surgery was successfully improved and fast-track extubation did not increase the re-intubation risk and other adverse events [54].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with early extubation had shorter ICU and hospital stays [37]. Ellis et al demonstrated that after implementing a fast-track extubation protocol, the number of early extubations after cardiac surgery was successfully improved and fast-track extubation did not increase the re-intubation risk and other adverse events [54].…”
Section: Discussionmentioning
confidence: 99%